Treatment protocols for hoof horn lesions and their impact on lameness recovery, pain sensitivity, and lesion severity in moderately lame primiparous dairy cows - Sadiq, Mohammed Babatunde; Ramanoon, Siti Zubaidah; Shaik Mohamed Mossadeq, Wan Mastura; Mansor, Rozaihan; Syed Hussain, Sharifah Salmah (Frontiers Research Foundation, 2022)
This study aims to investigate the effects of routine treatment protocols for claw horn disruptive lesions (CHDL) on lameness recovery rates, pain sensitivity, and lesion severity in moderately lame primiparous cows. A cohort of first parity cows was recruited from a single commercial dairy herd and randomly allocated to five treatments, comprising four lame groups (LTNB, LTN, LTB, and LT) and a single group non-lame group. Eligibility criteria for the lame cows included a first lameness score (score 3/5), presence of CHDL on a single foot, good body condition score of 3.0 to 3.5, and no history of previous lameness. LTNB received a combination of therapeutic trim, administration of a non-steroidal anti-inflammatory drug (NSAID; Ketoprofen) for 3 days, and hoof block on the healthy claw. Both LTN and LTB received the same treatment as LTNB without hoof block and NSAID, respectively. LT received only a therapeutic trim, whereas non-LT (negative control) received either a therapeutic or preventive trim. Pain sensitivity was assessed using the limb withdrawal reflex while lesion severity was recorded using the International Committee Animal Records (ICAR) Atlas guide. The enrolled cows were observed at weekly intervals, and the primary outcomes were assessed 28 days after treatment. The number (%) of recovered cows was 15 of 20 (75%), 13 of 21 (61.9%), 6 of 14 (42.9%), and 6 of 15 (40%) for LTNB, LTN, LTB, and LT, respectively. LTNB had significantly higher odds of successful treatment (OR = 4.5; 95% 1.1–19.1) compared to LT. Pain sensitivity based on limb withdrawal reflex was absent in a significantly higher number of cows (15/20; 75.0%) in LTNB compared to LTB and LT. LTB had a significantly lower lesion severity score in comparison to LTN. Overall, cows with limb withdrawal at day 28 after treatment were less likely (OR = 0.06; 95% CI 0.01–0.24) to develop a non-lame score. In conclusion, the treatment with therapeutic trim, hoof block, and NSAID led to better recovery and reduced pain sensitivity in moderately lame primiparous cows with good BCS compared to those that received only therapeutic trim. Further research on the changes within the hoof capsule following various treatment protocols is needed to elucidate the clinical benefits observed in this study.